Peran Pemerintah Desa dalam Pengelolaan Wisata Alam Negeri di Atas Awan di Desa Citorek Kidul Lebak Banten Berdasarkan Peraturan Daerah Nomor 2 Tahun 2016 tentang Penyelenggaraan Kepariwisataan - Amelia Susanti (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
Tourism is one of the natural resources owned by the Indonesian state. Lebak Regency, especially Citorek Village, has natural tourism from the Country Above the Clouds which is currently the center of attention of tourists, the development of the Country Above the Clouds natural tourism has had a positive impact and problems on the surrounding community, especially in Citorek Kidul Village. Thus the need to increase the role of the community and interested parties, especially the government in managing the country & natural tourism above the clouds, so that it becomes a tourist attraction that attracts tourists so as to increase the economic growth of the Citorek community. The author is interested in researching how the role of the village government in managing the country & natural tourism above the clouds in the village of Citorek Kidul Lebak Banten based on Regional Regulation Number 2 of 2016 concerning the Implementation of Tourism? and what is the licensing procedure for the management of natural tourism in the country above the clouds in the village of Citorek Kidul Lebak Banten based on Regional Regulation Number 2 of 2016 concerning the Implementation of Tourism?This study used an empirical juridical method with descriptive analytical research specifications. The data used in this study are secondary data supported by primary data in the form of interviews with the Head of the Tourism Destination Division of Lebak Regency and the Head of the Citorek Kidul Village who were analyzed descriptively qualitatively.The results of this study indicate that the role of the village government in managing natural tourism is still not optimal because the principle of independence and the principle of equality in Regional Regulation No.2 of 2016 concerning the Implementation of Tourism has not been fulfilled and there are several inhibiting and driving factors in the licensing process, the inhibiting factor is the source. Human power, namely the lack of understanding of the OSS system is still not evenly studied by the village community, the lack of facilities and infrastructure and lack of budgets, while the driving factor is the potential for tourism, namely the natural tourism of the country above the clouds which has the charm of a cloud that is witnessed on the mountain. sublime has a tourist attraction, community cooperation as social capital for the growth of natural tourism in the megeri above the clouds is formed by the presence of pokdarwis, support and motivation from the village government.